Clinical evaluation and management of endometriosis: guideline for Korean patients from Korean Society of Endometriosis - Hyejin Hwang; Youn-Jee Chung; Sa Ra Lee; Hyun-Tae Park; Jae-Yen Song; Hoon Kim; Dong-Yun Lee; Eun-Ju Lee; Mee-Ran Kim; Sung-Tack Oh (Korean Society of Obstetrics and Gynecology, 2018)
Endometriosis is one of the most common diseases in reproductive ages, and it affects patients' quality of life and fertility. However, few Korean guidelines are available for the evaluation and management of endometriosis. Korean Society of Endometriosis reviewed various literatures and trials, and to provide seventy-one evidence-based recommendations. This review presents guidelines for the diagnosis and management of endometriosis with emphasis on: it's role in infertility, treatment of recurrence, asymptomatic women, endometriosis in adolescents and menopausal women, and possible association of endometriosis with cancer.